TERAPI POTENSIAL DARI DIET SUPLEMEN NUTRISI DALAM PENCEGAHAN PENYAKIT VIRUS - Arnida Rahman; Sheira Indah Anjani; Risti Graharti (CV. Jasa Sukses Abadi, 2022)
The tremendous increase in infections caused by viruses and their mortality rate has demanded producing effective and safe antiviral drugs. Symptomatic treatment and immune enhancement are the most efficient methods because no specific drugs are available for every viral disease. Several naturally occurring compounds available have demonstrated antiviral potential in preventing and debilitating viral diseases. A nutrient-rich diet can help reduce many viral infections. Nutrients such as vitamins (vitamins A, D, C, E, B6, and B12) and elemental groups provide the highest nutritional value for all body systems, including bones, cardiovascular, liver, skin, and support immunity. This research provides information on dietary-based scientific recommendations, evidence, and case studies worldwide concerning a particular focus on viral infections. In this study, the use of bioactive compounds in viral mechanisms, particularly SARS and respiratory viral infections, will be discussed, which may help in facilitating preintervention either directly as supplements/fortified foods or in combination with pharmaceutical drugs. This research method reviews the immune potential in the content of dietary supplements based on laboratory studies and human research through international journals, trusted websites, and books in the last ten years. The result is that bioactive compounds such as vitamins, elements, and minerals with proven antiviral properties, in addition to pharmaceutical drugs themselves as dietary supplements, have been shown to play an important role in treating various infections caused by viruses and strengthening the immune system.